Osteosarcoma: Accelerating Progress Makes for a Hopeful Future - Saraf, Amanda J. (Front Oncol, 2018)
Patients who develop osteosarcoma in 2017 receive treatment that remains essentially unchanged since the 1970s. Outcomes likewise remain largely unimproved. Large, collaborative, multinational efforts to improve therapy have evaluated strategies leveraging both cytotoxic intensification and immunomodulatory agents. While these have confirmed our capacity to conduct such trials, results have proved largely disappointing. This has motivated efforts to focus on the basic biology of osteosarcoma, where understanding remains poor but has improved significantly. Recent advances have identified characteristic genetic features of osteosarcoma, including profound chromosomal disruption, marked patient-patient heterogeneity, and a paucity of recurrent mutations. Analyses suggest genesis in early catastrophic genetic events, although the nature of the inciting events remains unclear. While p53 and Rb inactivation occurs in most osteosarcomas, the landscape of associated driver mutations has proved extensive. Few mutations recur with high frequency, though patterns continue to emerge that suggest recurrent alterations within specific pathways. Biological pathways implicated in osteosarcoma biology through genetic and other preclinical studies include PI3K/mTOR, WNT/βcatenin, TGFβ, RANKL/NF-κB, and IGF. Unfortunately, clinical studies evaluating targeted agents have to date yielded disappointing results, as have studies examining modern immunotherapeutics. It remains unclear whether this pattern of clinical failures exposes inadequacies of our preclinical models, unrealistic expectations for single-agent responses in heavily pretreated patients, or biology less relevant than suggested. Nearly all patients who succumb to osteosarcoma develop lung metastases, which exhibit marked chemoresistance. Much scientific effort has recently sought to enhance our mechanistic understanding of metastasis biology. This research has potential to reveal novel targets for preventing and treating metastasis and for uncovering key vulnerabilities of osteosarcoma cells. Efforts to implement drug development strategies that leverage clinical studies in veterinary patients have potential to accelerate the translation of novel experimental regimens toward human studies. These could reduce costs and development timelines, prioritize agents, and refine regimens prior to human clinical trials. The rise of philanthropic groups focused on osteosarcoma has enhanced cross-disciplinary and cross-institutional focus and provided much needed resources. Transformative new therapies will likely arise from collaborative, interdisciplinary efforts that extend our understanding of osteosarcoma’s most basic inner workings.